Peran Strategi Pemasaran dalam Memoderasi Pengaruh Gaya Hidup dan Kualitas Produk terhadap Keputusan Pembelian Kopi pada Mahasiswa di Kota Semarang - Tomy Ledianto; Siti Sumiati (Lembaga Yasin AlSys, 2026)
The increasing consumption of coffee among university students has made coffee shops not only places to enjoy beverages but also part of their lifestyle. However, studies examining the role of marketing strategy in moderating the effects of lifestyle and product quality on coffee purchasing decisions among university students remain limited. This study aimed to analyze the effects of lifestyle and product quality on purchasing decisions, with marketing strategy as a moderating variable, among university students in Semarang City. The study employed a quantitative approach with a verificative design and involved 100 respondents selected through purposive sampling, with the criterion that they had purchased products from coffee shops at least twice. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that lifestyle and product quality had positive and significant effects on purchasing decisions. Marketing strategy was also found to strengthen the effects of lifestyle and product quality on purchasing decisions; therefore, all research hypotheses were accepted. These findings confirm that university students’ purchasing decisions are determined not only by lifestyle and product quality but are also strengthened by the implementation of effective marketing strategies through promotion, venue comfort, and marketing communication aligned with consumer characteristics. Therefore, coffee shop operators need to integrate an understanding of consumer lifestyles, improvements in product quality, and the implementation of appropriate marketing strategies to encourage purchasing decisions.